Media Augmented Reality untuk Meningkatkan Literasi Sains dan Kemampuan Metakognitif Kelas V SD - I Putu Gilang Leo Agusta (Universitas Pendidikan Ganesha, 2022)
Student activity is still very lacking, and the application of literacy only relies on textbooks. This research aims to develop Augmented Reality media to improve scientific and metacognitive literacy for fifth-grade elementary school students. This type of research is the development of the ADDIE model. The research subjects are two media experts and two learning content experts. The test subjects were 25 and 2 teachers—collecting data using interviews, questionnaires, tests, and observations. The data collection instrument uses a rating scale. The analysis technique uses qualitative and quantitative analysis methods and inferential statistical analysis. The study results are the assessments made by material experts get 4.85 (very good) and media experts 4.83 (very good). The teacher's response validation results are 4.62, and the student's response is 4.7, so it is very good. The hypothesis test results are obtained with a significance of 0.000, tested together and separately, so there is a significant difference between scientific literacy and metacognitive ability. It was concluded that Augmented Reality could improve scientific and metacognitive literacy.